2006
DOI: 10.1038/nrn1937
|View full text |Cite
|
Sign up to set email alerts
|

A clustered plasticity model of long-term memory engrams

Abstract: Long-term memory and its putative synaptic correlates the late phases of both long-term potentiation and long-term depression require enhanced protein synthesis. On the basis of recent data on translation-dependent synaptic plasticity and on the supralinear effect of activation of nearby synapses on action potential generation, we propose a model for the formation of long-term memory engrams at the single neuron level. In this model, which we call clustered plasticity, local translational enhancement, along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
317
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(344 citation statements)
references
References 105 publications
24
317
1
2
Order By: Relevance
“…They found that the consolidation of either LTP or LTD (capture of LTP or LTD) was facilitated in response to the previous induction of the late phase of the opposite form of synaptic plasticity in a separate population of synapses in the same neurons ( Figure 2L), a paradoxical phenomenon they originally referred to as "cross-tagging" (Sajikumar and Frey, 2004a), although it has been later renamed as "cross-capture" by other authors (Govindarajan et al, 2006;Morris, 2006), a term we also consider more appropriate. In this case, the situation seems to be radically different to that described in Aplysia cultured neurons, in which LTD overrides, instead of facilitate, LTF (Guan et al, 2002).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the consolidation of either LTP or LTD (capture of LTP or LTD) was facilitated in response to the previous induction of the late phase of the opposite form of synaptic plasticity in a separate population of synapses in the same neurons ( Figure 2L), a paradoxical phenomenon they originally referred to as "cross-tagging" (Sajikumar and Frey, 2004a), although it has been later renamed as "cross-capture" by other authors (Govindarajan et al, 2006;Morris, 2006), a term we also consider more appropriate. In this case, the situation seems to be radically different to that described in Aplysia cultured neurons, in which LTD overrides, instead of facilitate, LTF (Guan et al, 2002).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a recent review article, Tonegawa's group developed the "clustered plasticity hypothesis" to explain memory encoding at the single neuron level (Govindarajan et al, 2006). This model, contrary to previous computational models that relied on associational LTP and LTD as the predominant mechanism for memory formation, added local enhancement of protein synthesis, STC to explain the formation of long-term memory engrams through bidirectional synaptic weight changes among synapses within or across dendritic branches.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Because NMDA receptor activation affects microtubule growth inside the dendritic shaft, it could transiently decrease the microtubule content of neighboring spines and enhance their response to subsequent NMDA receptor stimulation. These mechanisms could contribute to so-called clustered plasticity, which means that similar long-term synaptic changes are more likely to occur at spines that are clustered on one dendritic branch (Govindarajan et al, 2006). Future experiments will be required to determine the in vivo importance of persistent suppression of microtubule dynamics and examine the duration of suppression required to influence long-term structural changes in the brain.…”
Section: The Effect Of Cytoskeletal Changes On Spine Morphologymentioning
confidence: 99%
“…To address this biological problem, it was suggested that a transient local synaptic tag is established at those recently activated synapses where PRPs are specifically captured. This idea was originally postulated by Frey and Morris (6) and it is now known as the synaptic tagging and capture (STC) hypothesis (7)(8)(9). In their seminal work they showed that early-LTP, a transient form of LTP that is induced by a weak stimulus, could be extended to late-LTP, a more persistent form of LTP, if the weak and the strong stimuli were applied in a relatively long-lasting associative time window on different synapses of the same neuron.…”
mentioning
confidence: 99%